The influence of full-time, clinical placements on the emotional intelligence of therapy students - Gribble, Nigel; Ladyshewsky, Rick; Parsons, Richard (2019)
Background: Emotional intelligence (EI) skills are essential to therapy students as they participate in full-time clinical placements. No previous research had explored if, and how, clinical placements influenced therapy students’ EI skills. Methods: The study used a longitudinal, sequential explanatory, mixed methods design. Participants were undergraduate occupational therapy, physiotherapy, and speech pathology students (n=296). Business students (n=93) were included as a control group because they undertake no workplace placements. The Emotional Quotient Inventory 2.0 tracked the changes in EI scores measured at three-time points over the final 16 months of their undergraduate university program. Interviews were conducted with 24 students to determine if, and how, clinical placements influenced the changes in EI skills. Results: Before students commence full-time placements, four EI skillsets were significantly lower than the Australian Population Norms. However, after their clinical placements were completed, therapy students’ Total Emotional Intelligence score increased significantly, as well as 10 other skills. The business students showed no significant EI changes. During interviews, the students agreed that 95% of changes in EI skills were directly related to their clinical placements. The key influences on EI during clinical placements were: supervisory style, the student’s interacting with patients, reflecting on and receiving feedback on EI skills from clinical supervisors. Discussion: Our study contributes new knowledge to clinical supervisors, university educators, and employers of new therapy graduates. Clinical supervisors are recommended to role model an array of EI skills to students, allow students to work closely with patients experiencing complex emotional distress, be emotionally in-tune and engaged with students, and to trust the students to work autonomously with patients in emotional turmoil. Supervisors are encouraged to give students and new graduates feedback on their EI skills.